Dove exiled - Bao, Karen (New York, New York : Viking, 2016)
After fleeing the Moon, fifteen-year-old Phaet Theta hides on Earth and plots how to rescue her siblings from the wrath of the Lunar government.
Sequel to: Dove arising.
Ages 12 up.
Keywords: Science fiction; Space colonies -- Fiction; Militia movements -- Fiction; Government, Resistance to -- Fiction; Youths' writings; Moon -- Fiction